Flight operational quality assurance for very light jets - Marc Leon Alfred Meuleman Filho (2009)
The introduction of Very Light Jets (VLJ) worldwide in the modern aviation environment represents a potential challenge in terms of safety and investigation. The VLJs are intended to be flown by a single pilot and carry a high level of automation, with state of the art glass cockpits and extensive use of onboard software. Although in some cases it is not even mandatory for them to carry a CVR/FDR, some manufacturers choose to provide these recorders for their VLJ in order to improve the safety and investigation resources. The FDR will be more limited than the ones used in commercial aviation, but, nonetheless, will open the possibility for some important safety monitoring programs, like Flight Operational Quality Assurance (FOQA). This study describes modern VLJs and recorder systems, then covers the selection of the parameters for the FDR dataframe of a VLJ and proposes the structure of a FOQA program for this type of aircraft, taking as example the EMBRAER Phenom 100. The events to be monitored by this program are summarized and applied to real incidents and accidents that occurred with VLJs in order to show how FOQA can help preventing them.